2021
DOI: 10.1186/s13046-021-01831-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C sensitizes BRAFV600E thyroid cancer to PLX4032 via inhibiting the feedback activation of MAPK/ERK signal by PLX4032

Abstract: Background BRAFV600E mutation is the most common mutation in thyroid cancer. It strongly activates MAPK/ERK pathway and indicates an invasive subtype of thyroid cancer. PLX4032 is a selective oral inhibitor of the BRAFV600 kinase although with limited effect in treating this panel of thyroid cancer, due to the feedback activation of MAPK/ERK as well as PI3K/AKT pathways. It was investigated that Vitamin C plays a positive role in inhibiting these pathways in thyroid cancer. However, whether Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Similarly, a remarkable kinase modulator effect was observed in several studies, mostly by reducing phosphorylation levels of ERK, BRAF and AKT [ 64 , 99 , 109 , 122 , 123 ] (Figs. 2 and 4 ).…”
Section: Anti-cancer Mechanismssupporting
confidence: 60%
See 3 more Smart Citations
“…Similarly, a remarkable kinase modulator effect was observed in several studies, mostly by reducing phosphorylation levels of ERK, BRAF and AKT [ 64 , 99 , 109 , 122 , 123 ] (Figs. 2 and 4 ).…”
Section: Anti-cancer Mechanismssupporting
confidence: 60%
“…Similarly, resistance to BRAFV600 inhibitor vemurafenib was also abrogated by VitC in melanoma in vivo [ 123 ]. Recent findings reinforce the promising synergistic effects of VitC with kinase inhibitors such as BRAFV600 inhibitor PLX4032 in thyroid cancer in vivo [ 64 ] and with BTK inhibitor ibrutinib and PI3K inhibitor idelalisib in chronic lymphocytic leukemia (CLL) patient-derived cells [ 104 ].…”
Section: High-dose Vitc In Combination Treatmentsmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, a recent in vitro study performed on BRAF V600E-positive TC cell lines indicated antiproliferative and re-differentiative effects of dabrafenib and vemurafenib [ 131 ]. Moreover, vemurafenib-treated BRAF V600E-positive PTC cells exhibited an increased apoptosis level [ 132 ], whereas ascorbic acid (vitamin C) was found to sensitize BRAF V600E-positive thyroid cancer cells to this agent [ 133 ]. Recent reports suggest, that co-therapy based on dabrafenib and trametinib may lead to durable disease control and prolonged benefit in patients with a BRAF -mutated PTC [ 134 ].…”
Section: Currently Used and Investigated Targeted Therapies In Tcsmentioning
confidence: 99%